THE USE OF YOUTUBE TO TEACH INTERCULTURAL COMMUNICATION - Lini Fitri (Jurnal Ilmiah Spectral, 2022)
Teaching media as supporting facilities is one of the important parts that must be provided because it improves teaching performance in implementing the learning activity. In connection with technology developments, teachers can choose one of the technology media that suits the teaching objective or motivates the students to be autonomous learners. Therefore, this study attempts to promote the possibility of using Youtube videos in the teaching-learning process, especially in teaching intercultural communication to EFL learners. By using Youtube videos, teachers can show the cultural context that is relevant to the language being taught so it can provide an interactive learning environment and motivate students to learn faster and better.